Determining the Level of Perceived Risk in e-business Web 2.0 Interactions - Hussain, Omar; Chang, Elizabeth; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
While making an interaction-based decision in the domain of e-commerce business interactions, it is important for the initiating agent of the interaction to analyze and consider the level of perceived risk in forming an interaction with an agent, apart from just considering the level of trust. By doing so the initiating agent would have all the concepts which would assist it in making an informed interaction-based decision in that domain. But for risk analysis in e-business interactions, it is important that the initiating agent considers and assesses the level of perceived risk in the interaction according to its object of analysis in that domain. In our previous work, we have identified the sub-categories of perceived risk in the domain of e-business interactions and proposed methodologies by which the initiating agent assesses and quantifies them. In this paper, we propose a novel approach by which the initiating agent by utlizing the determined sub-categories assesses and quantifies the numerical level and magnitude of perceived risk in forming an interaction with an agent.